FAKTOR YANG MEMPENGARUHI PENYESUAIAN DIRI PESERTA DIDIK - Warer, Puja - (Bimbingan dan Konseling, 2014)
This research was based on the observation which found that a students are not able toadaptation with their environment, they still have a negative perception about phisycal that their areshort, their skin are black and psychological that lack of confidence to make asocial interaction withtheir friends and because of that their become an individual and underestimated by their friends. Thepurpose of this research is to describe: 1) Factor which influences students adaptation is physicalappearance 2) Factor which influences students adaptation is personality 3) Factor whinch influencesstudents adaptation is education 4) Factor whinch influences students adaptation is environment. Thiskind of research is classified as descriptive research.The population of this research is IX gradestudents numbered 242 people. This research used proportional random sampling method. Thesampel of this research was 71 students. to collect data us questionalre. Mean while, the data analysisused kriterium Sturgess formula and percentage analysis technique. The result of this research revealsthat 1. Factor which influences students adaptation can be seen from the physical appearece is quite1)factor which influences students adaption can be seen from the physical appearance is quite a let 2)factor which influences students adaption can be seen from their persenelity is in greas quantition 3)factor which influences students adaption can be seen from their aducation 4) factor which influencesstudents adaption can be seen from their envirenment is quite a let.